Atrial strain in cardiacATTR amyloidosis from pathophysiology to prognosis: is it time to rethink our approach to disease?. (25th November 2020) - Bandera, F; Martone, R; Chacko, L; Ganesananthan, S; Lane, T; Martinez-Naharro, A; Whelan, C; Quarta, C; Rowczenio, D; Gilbertson, J.A; Lachmann, H; Guazzi, M; et al.
Abstract: Background: Left atrial (LA) involvement in cardiac ATTR amyloidosis (ATTR-CM) has never being explored. The aim of the study is to characterize the spectrum of changes in LA structure in ATTR-CM, the functional consequences on LA mechanics and the association with mortality. Methods: We studied 936 patients with ATTR-CM who underwent prospective protocolized evaluations comprising ECG, full echocardiographic assessment, 6MWT, blood biomarkers sampling and survival assessment between 2000 and 2019. Reservoir (LAr), conduit (LAcd) and booster (LAcont) function were assessed according to current guidelines. LA stiffness (LAstiff) was estimated as the ratio between E/e' and LAr. The presence and extent of amyloid infiltration was assessed in two autopsied hearts from patients ATTR-CM with congo red staining and TTR antibodies. Results: 936 patients with ATTR-CM were included, 567 with wtATTR-CM and 346 with hATTR-CM, of whom 246 had the V122I variant and 100 the T60A variant. LA indexed area was similar across the 3 genotypes, whilst LAr, LAcd and LAcont were significantly reduced in V122I patients compared to Wt and T60A patients (LAr: 10.4±6.4 vs 12.8±8.5 vs 8.59±5.7%, p<0.0001; LAcd: 5.6±5.0 vs 6.9±5.7 vs 4.0±3.6%, p<0.0001; LAcont 7.5±4.1 vs 8.2±4.9 vs 6.7±4.2%, p=0.023; in Wt, T60 and V122I respectively). Similarly, LAstiff was significantly worse in V122I compared to Wt and T60A (LAstiff: 2.39±2.62 vs 2.59±4.83 vs 2.96±2.88, p<0.0001, in Wt, T60 and V122I respectively). In the overall population, LAstiff remained independently associated with mortality, after adjusting for rhythm, systolic and diastolic functional parameters, ventricular longitudinal strain, genotypes, clinical variables and NAC staging system (lnLA stiff: HR=1.26, CI: 1.07–1.57; p=0.009). In the overall population, 584 patients were in sinus rhythm and 344 in atrial fibrillation, atrial flutter or atrial tachycardia (non-sinus rhythm group – NSR). Among patients in SR, 21.6% did not show a measurable LA mechanical contraction on strain analysis (LAcont). Patients in SR without LAcont on strain analysis showed similar structural and functional LA changes, NTproBNP, NYHA class, and 6MWT to NSR patients. Mortality of patients in SR with no LAcont was significantly reduced compared to patients in SR with LAcont and similar to patients in AF (Figure 1). On the two autopsies hearts there was extensive amyloid infiltration of TTR type in the atrial wall as confirmed with CR and TTR antibodies (Figure 1). Conclusions: ATTR-CM is characterized by primary infiltration of the atrial walls with progressive loss of atrial function and increased stiffness. LA stiffness is a strong independent predictor of mortality after adjusting for known predictors. Atrial electro-mechanical dissociation emerged as a distinctive functional phenotype identifying patients in SR with worse prognosis. Funding Acknowledgement: Type of funding source: None